2021
DOI: 10.1002/biot.202100514
|View full text |Cite
|
Sign up to set email alerts
|

CRISPRa/i with Adaptive Single Guide Assisted Regulation DNA (ASGARD) mediated control of Chlorella sorokiniana to enhance lipid and protein production

Abstract: Chlorella species are indispensable microalgae for biorefinery but are hardly in DNA manipulation due to the high guanine‐cytosine (GC) contents of DNA. In this study, we established a new approach via 20 guanines for sgRNA design, which is annotated as “Adaptive Single Guide Assisted Regulation DNA (ASGARD)” and coupling with CRISPR interference associated dCas9 system to overcome the difficulties. At first, C. sorokiniana was predominate as its faster growth rate when compared to C. vulgaris and C. variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The U.S. Food and Drug Administration (FDA) authorized C. reinhardtii microalgae for human consumption, and it was widely utilized for the manufacture of protein. [176][177][178] Genetic modification of this strain allowed it to effectively accumulate zeolin (chimeric recombinant protein of zein and phaseolin, the major seed storage proteins from maize and beans), thus creating a promising platform for protein production. [66] Remarkably, compared to individual proteins, the zein and phaseolin chimera have a better balanced amino acid composition.…”
Section: Gene Engineering and Selection Of Microalga For Food And Pig...mentioning
confidence: 99%
“…The U.S. Food and Drug Administration (FDA) authorized C. reinhardtii microalgae for human consumption, and it was widely utilized for the manufacture of protein. [176][177][178] Genetic modification of this strain allowed it to effectively accumulate zeolin (chimeric recombinant protein of zein and phaseolin, the major seed storage proteins from maize and beans), thus creating a promising platform for protein production. [66] Remarkably, compared to individual proteins, the zein and phaseolin chimera have a better balanced amino acid composition.…”
Section: Gene Engineering and Selection Of Microalga For Food And Pig...mentioning
confidence: 99%
“…The Cas9/single guide RNA (sgRNA) RNP delivery enhanced the HDR at the nitrate reductase (NR) target site, generating ∼70% of positive mutant lines, indicating a significant improvement in editing efficiency compared to the native HDR system alone. Additionally, Lin et al (2021) developed a novel approach to designing sgRNA via 20 guanines, called Adaptive Single Guide Assisted Regulation DNA (ASGARD) and coupled it with the dCas9 system in C. sorokiniana . Among the transformants, this approach led to an increase in protein content, reaching up to 60% (w/w) of DCW, with the highest protein concentration being 570 mg/L ( Lin et al, 2021 ).…”
Section: Microalgae For Sustainable Bioeconomymentioning
confidence: 99%
“…Additionally, Lin et al (2021) developed a novel approach to designing sgRNA via 20 guanines, called Adaptive Single Guide Assisted Regulation DNA (ASGARD) and coupled it with the dCas9 system in C. sorokiniana . Among the transformants, this approach led to an increase in protein content, reaching up to 60% (w/w) of DCW, with the highest protein concentration being 570 mg/L ( Lin et al, 2021 ). In another study, the authors developed a CRISPR-Cas9 reverse-genetics pipeline and used it to identify a TF that regulates lipid accumulation, called ZnCys, in Nannochloropsis gaditana (CCMP 1894) ( Ajjawi et al, 2017 ).…”
Section: Microalgae For Sustainable Bioeconomymentioning
confidence: 99%
“… Lin et al (2022) used CRISPRa/i system to modulate the gene expression in Chlorella sorokiniana UTEX 1602. They demonstrated that gene regulation via dCas9-VP64 (CRISPRa) increased the protein contents by approximately 60% (w/w), while that via dCas9-KRAB (CRISPRi) increased the protein content to 65%, and lipid accumulated in the range of 150–250 mg/L (WT: 150 mg/L).…”
Section: Crispr/cas As a Genome Engineering Toolmentioning
confidence: 99%
“…The mutants were negatively selected on potassium chlorate or 2-fluoroadenine clearly exhibiting the practicality of generating markerless mutants in Chlorella that might likely not fall under regulatory purview (Kim et al, 2021). Lin et al (2022) used CRISPRa/i system to modulate the gene expression in Chlorella sorokiniana UTEX 1602. They demonstrated that gene regulation via dCas9-VP64 (CRISPRa) increased the protein contents by approximately 60% (w/w), while that via dCas9-KRAB (CRISPRi) increased the protein content to 65%, and lipid accumulated in the range of 150-250 mg/L (WT: 150 mg/L).…”
Section: Chlorella Sppmentioning
confidence: 99%